The repeatability of three diagnostic methods (visual using ICDAS II, laser fluorescence, and radiographic) for early caries detection - Sukmasari, Susi; Lestari, Widya; Ko, B B; Mohf Noh, Nur Zety; Asmail, N; Yaacob, Munirah (IOP, 2017)
Newly introduced ICDAS II as a visual method, laser fluorescence as another technique that have ability to quantify early mineral loss of tooth structure and intra oral radiograph, are methods can be used in the clinic. To provide standardization for comprehensive caries management at an early stage, all methods supposed to be tested between users. The objective of this research is to evaluate the repeatability of each system. It is a comparative cross sectional study using 100 extracted permanent teeth without obvious cavitation (premolar & molar) that were collected and stored in thymol solution. The teeth were embedded on the wax block and labeled with numbers. All 5 surfaces were examined by 5 examiners using visual (ICDAS II), laser fluorescence (LF) and radiographic examination. The data were then analyzed to measure intra and inter examiner repeatability using Cronbach’s alpha and inter-item correlation matrix. Intra-examiner repeatability for all examiners was >0.7. Chronbach’s α value for inter-examiner repeatability for ICDAS II was >0.8 on 3 surfaces except on buccal and lingual. LF exhibit repeatability of >0.8 on all surfaces. Radiograph shows a low value of inter examiner repeatability (<0.7). Lecturer examiners showed the highest agreement followed by undergraduate students for inter-item correlation while the 2nd and 3rd reading of LF displays the best agreement. ICDAS II score favors more non-invasive treatment compared to LF. ICDAS II showed good repeatability except on buccal and lingual surfaces. In line with some of the previous study, ICDAS II is applicable for caries detection in daily clinical basis. Laser fluorescence exhibits the highest repeatability while the radiograph showed weak interexaminer repeatability. Treatment decisions of ICDAS II propose more preventive treatment for early caries lesions compared to laser fluorescence.